Epidemiology of Dermatophyte Infections in Palestine: an update Study - Eman Yousef Mohammed Hussein (My University, 2013)
Background: Dermatophytes are a group of morphologically and physiologically related molds some of which cause well defined infections: dermatophytoses (tineas or ringworm) .They have two important properties: they are keratinophilic and keratinolytic. This means they have the ability to digest keratin in vitro in their saprophytic state and utilize it as a substrate and some of them can invade tissues in vivo and cause tineas. Objectives: This study was designed to determine the epidemiology including prevalence and occurrence of causative agents of dermatophytosis in patients in Palestine; detecting any changes in the etiological agents during the last 28 years; studying the effective factors such as socioeconomic condition, age, contact with animals and others; studying the correlation between multifocal infections tinea pedis , tinea nail and tinea cruris. The study was also aimed at genotyping identification and how can be used as a molecular tool for rapid diagnosis for dermatophytes also to study the diversity during different dermatophytes species and within the same specie specially Microsporum canis, Trichophyton rubrum and Trichophyton mentagrophytes. Genetic studies by random amplification of polymorphic DNA (RAPD) have been used to detect polymorphism of dermatophytes. The genotypical analysis was performed using the RAPD method as rapid molecular tool for diagnosis. Results: In this study, a total number of 220 samples from 188 patients were examined ((137 males (72.9%), and 51 females (27.1%)). Tinea Capitis (27.7%) was the predominant clinical manifestation followed by tinea pedis (23.4%), tinea nail (22.3%), tinea cruris (20.2%) and tinea corporis(6.4%). The dominant causative agent was Microsporum canis 104 samples from 138 (75.36%) followed by Trichophyton rubrum 31 samples from 138 (22.5%) then Trichophyton mentagrophytes 3 samples from 138 (2.1%). The RAPD results showed that all analyzed strains are mainly from three genotypes of Microsporum canis, two genotypes of Trichophyton rubrum and one genotype of Trichophyton mentagrophytes. Thus, based on analysis of the RAPD data, a correlation can be shown between the genotypical patterns of the strains of Microsporum canis also between the strains of Trichophyto rubrum and Trichophyton mentagrophytes from Palestine. Conclusions: The results showed that the predominant causative agent of dermatophytes specis was Microsporum canis. This change could be due to several factors as activity related to human and animals’ hygiene, interaction between human and human, animal and soil, and changing population over the times.

خلفية: الفطريات الجلدية هي مجموعة من القوالب الفطرية ذات طرز شكلية وفسيولوجية مرتبطة مع بعضها البعض، تسبب التهابات واضحة المعالم (القوباء الحلقية)، لديهم خاصيتان تعتبران من الخصائص الهامة بالنسبة للفطريات وهما: أن هذه المجموعة من الفطريات لديها القدرة على الارتباط وهضم الكيراتين والاستفادة منه باعتباره الركيزة الأساسية للغذاء لذلك يمكن لبعضها أن يغزو الأنسجة المحتوية على الكيراتين في جسم الكائن الحي مسببة له القوباء أو الأمراض الجلدية. الأهداف: تم تصميم هذه الدراسة لتحديد وبائية الفطريات الجلدية ( (Dermatophytes، بما في ذلك انتشارها ووجود العوامل المسببة للفطريات الجلدية للمرضى في فلسطين؛ والكشف عن أية تغييرات في العوامل المسببة خلال ال 28 عاما الماضية؛ كما وتهدف هذه الدراسة أيضا،إلى دراسة العوامل المؤثرة في انتشار المرض مثل الظروف الاجتماعية والعمر والتعامل مع الحيوانات وغيرها من العوامل المسببة للمرض؛ و دراسة العلاقة بين التهابات متعددة البؤر وهي سعفة القدم، سعفة الأظافر و سعفة الفخدين في الشخص الواحد وإذا ما كان المسبب واحدا في كل الحالات،كما وتهدف هذه الدراسة أيضا إلى تقييم العلاقة المحتملة بين الأنماط الجينية المختلفة بين السلالات المختلفة المعزولة من الفطريات الجلدية التي تصيب الإنسان في فلسطين.ومعرفة مدى إمكانية استخدام الطريقة الجزيئية لتشخيص الفطريات الجلدية تشخيصا سريعا ودقيقا ومن أهداف هذه الدراسة أيضا دراسة التنوع الجيني بين الأنواع والأصناف المختلفة وداخل النوع والصنف الواحد خاصة من الفطريات الجلدية المعزولة وهي Microsporum canis, , Trichophyton rubrum and Trichophyton mentagrophytes الدراسة على المستوى الجزيئي كانت باستخدام تقنية التضخيم العشوائي من الحمض النووي متعدد الأشكال (Random Amplification of Polymorphic DNA (RAPD) للتحقيق في العلاقات الوراثية بين السلالات المختلفة وكيف يمكن استخدامها كأداة جزيئية للتشخيص السريع لأمراض الجلدية المختلفة. النتائج: في هذه الدراسة، كان العدد الإجمالي للعينات الذي فحص220من 188 مريض، 137 من الذكور (72.9%) و 51 من الإناث (27.1٪). سعفة الرأس (27.7٪) هو مظهر من مظاهر السريرية الغالبة تليها سعفة القدم (23.4٪)، سعفة الأظافر (22.3٪)، سعفة الفخدين (20.2٪) وسعفة الجسم (6.4٪). وكان العامل المسبب السائد هو Microsporum canis104 عينات من 138 (75.36٪) وأظهرت النتائج أن جميع السلالات التي تم تحليلها باستخدام RAPD أنها أساسا تعود لثلاث أنماط جينية متصلة وراثيا وجينيا معا. يليه العامل المسبب الثاني وهو Trichophyton rubrum يتكون من نمطين جينيين وأخيرا Trichophyton mentagrophytes يتكون من نمط جيني واحد. وبالاعتماد على تحليل البيانات والنتائج وجد أن ثمة علاقة وثيقة تربط بين النمط الجيني والنمط الشكلي لكل سلالة من السلالات الفلسطينية المعزولة. الاستنتاجات: أظهرت النتائج أن العامل المسبب السائد للإصابة الفطرية الجلدية كان Microsporum canis. وهذا تغير كبير في مسبب الإصابة المرضية؛ ويمكن أن يكون هذا التغير نتيجة لعدة عوامل مثل التغير في النشاط الذي يمارسه الإنسان مؤخرا والتفاعل بين الإنسان والحيوان والتربة وما يتعلق بالإنسان والنظافة، وتغيير عدد سكان والهجرة في الثلاث عقود الماضية. كما وأوصت الدراسة باتخاذ التدابير الوقائية اللازمة لتجنب مسبب المرض والتوجه للطبيب مباشرة فور الإصابة بالمرض.
وبائية الأمراض الجلدية في فلسطين: دراسة للتحديث